2021
DOI: 10.3390/ijms22158040
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical Properties of N-Oxide Surfactants—Two in One

Abstract: Surfactants are molecules that lower surface or interfacial tension, and thus they are broadly used as detergents, wetting agents, emulsifiers, foaming agents, or dispersants. However, for modern applications, substances that can perform more than one function are desired. In this study we evaluated antioxidant properties of two homological series of N-oxide surfactants: monocephalic 3-(alkanoylamino)propyldimethylamine-N-oxides and dicephalic N,N-bis[3 ,3′-(dimethylamino)propyl]alkylamide di-N-oxides. Their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Pyridine- N -oxide has been shown to have similar properties as the tyrosine/tyrosyl radical redox couple and can thus serve as an electron shuttle in artificial photosynthesis (Figure D). , Along the same lines, polymeric N -oxides have been found to have special electron transport properties useful for the construction of semiconducting polymers and interlayer materials for organic solar cells . This special radical reactivity might also be the reason for the antioxidant properties, which have been suggested for several amphiphilic N -oxides used in cosmetic applications. , …”
Section: Properties Of N-oxidesmentioning
confidence: 84%
“…Pyridine- N -oxide has been shown to have similar properties as the tyrosine/tyrosyl radical redox couple and can thus serve as an electron shuttle in artificial photosynthesis (Figure D). , Along the same lines, polymeric N -oxides have been found to have special electron transport properties useful for the construction of semiconducting polymers and interlayer materials for organic solar cells . This special radical reactivity might also be the reason for the antioxidant properties, which have been suggested for several amphiphilic N -oxides used in cosmetic applications. , …”
Section: Properties Of N-oxidesmentioning
confidence: 84%
“…The in vitro cytotoxicity evaluation of the studied nanoemulsions was performed using a 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) cell viability assay as in our previous studies [ 12 , 34 ]. For the experiments, human skin cells were removed by trypsinization (trypsin 0.025% and EDTA 0.002% solution) and rinsed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…It is now well established that theoretical methods are an efficient multipurpose tool for chemistry, biochemistry, and material science. Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%